Sosialisasi Peningkatan Kualitas Pelayanan Koperasi Harapan Sejahtera-19, Bekasi - Ktut Silvanita Mangani; Arko Pujadi; Saut Pane; Norman Edy; Rini Yulia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2022)
The progress of the cooperative business is influenced by the management pattern, type of the business, capital, activity of its members, and others. Therefore, a cooperative needs to know whether the cooperative implemented a good management pattern and produces good performance, and meets the expectations of its members. This Community Service (PkM) activity is a socialization of the results of a survey on the service performance of the Cooperative of Harapan Sejahtera-19 towards the expectations of the residents of RW 19 Graha Harapan Housing, Mustika Jaya Village, East Bekasi. By knowing the opinions of the members and the community involved in the cooperative's activities, then the cooperative can improve its performance to meet the expectations of its customers. The method is to describe service performance and service satisfaction, then analyze them using a Cartesian diagram. Based on the diagram, then produces recommendations for the development of the Cooperative of Harapan Sejahtera-19. Input for cooperative management is about clarity of information related to cooperative performance as well as easier loan procedures and requirements. Keywords: Cooperative; service performance; services satisfaction